Factors associated with functional disability of elderly in Brazil: a multilevel analysis - Alves, Luciana Correia; Leite, Iúri da Costa; Machado, Carla Jorge (Revista de Saúde Pública, 2010)
OBJECTIVE: To analyze the influence of demographic, socioeconomic, health, and contextual factors of the Brazilian federation units on the functional disability of the elderly. METHODS: Cross-sectional study based on data from the 2003 PNAD (Brazilian National Household Survey), of IBGE (Brazilian Institute of Geography and Statistics) and Ipea (Institute of Applied Economic Research). The sample was composed of 33,515 individuals aged 60 years and older. The dependent variable was functional disability, measured by difficulty in climbing slopes or stairs. The independent variables were divided into two levels: individual (demographic, socioeconomic and health-related characteristics) and contextual (Gini Index and Gross Domestic Product per capita by Brazilian state in 2000). A multinomial and multilevel logistic regression model was utilized in order to estimate the effect of the independent variables on the functional disability of the elderly. RESULTS: Functional disability was associated with demographic, socioeconomic and health factors. At the individual level, sex, level of schooling, income, occupation, self-perception of health and chronic diseases were the factors that were most strongly related to functional disability. At the contextual level, income inequality proved to exert an important influence. CONCLUSIONS: Self-perception of health is the factor that is most strongly related to the functional disability of the elderly in Brazil, followed by chronic diseases. Sex, occupation, level of schooling and income are also highly associated with it. Actions that approach the main factors associated with functional disability can contribute significantly to the well-being and quality of life of the elderly.